ASSOCIATIVISM AMONG URBAN WASTE PICKERS IN BRAZIL - Marília Veronese; Julice Salvagni (Revista Gestão e Desenvolvimento, 2024)
The article is based on the Sociopoetics methodology and is theoretically supported by Boaventura de Sousa Santos’ critical sociology, especially the sociology of absences and emergencies and the prospect of Epistemologies of the South. It was conducted with recycling cooperatives in the city of Canoas, southern Brazil. The object is the knowledge and social practices produced in contexts of collective life among poor workers who have in the association to collection and treatment of urban recyclables an alternative to improve their living conditions. Knowledge involves perceptions and representations covering identity and sociocultural expressions of these subjects. The research conducted so far shows that precariousness and social disqualification remain in their daily experiences; economic inclusion is limited, and the obtained income is not always enough. There is, however, the ability to produce processes of change in their living conditions by entering in a context of political participation and access to public policies.